Exploring global research trends in Chinese medicine for atherosclerosis: a bibliometric study 2012–2023 - Tan, Moye; Wang, Jiuyuan; Chen, Zhengxin; Xie, Xuejiao (Frontiers in Cardiovascular Medicine, 2024)
Background: While Traditional Chinese Medicine (TCM) boasts an extensive historical lineage and abundant clinical expertise in addressing atherosclerosis, this field is yet to be penetrated adequately by bibliometric studies. This study is envisaged to evaluate the contemporary scenario of TCM in conjunction with atherosclerosis over the preceding decade while also identifying forthcoming research trends and emerging topics via the lens of bibliometric analysis.Methods: Literature pertaining to TCM and atherosclerosis, circulated between January 1, 2012 and November 14, 2023, was garnered for the purpose of this research. The examination embraced annual publications, primary countries/regions, engaged institutions and authors, scholarly journals, references, and keywords, utilizing analytical tools like Bibliometrix, CiteSpace, ScimagoGraphica, and VOSviewer present in the R package.